Detecting discrimination in the hiring process: Evidence from an internet-based search channel - Stefan Eriksson; Jonas Lagerström (Institute for Labour Market Policy Evaluation (IFAU), 2007)
This paper uses data from an Internet-based CV database to investigate how factors which may be used as a basis for discrimination, such as the searchers' ethnicity, gender, age and employment status, affect the number of contacts they receive from firms. Since we have access to essentially the same information as the firms, we can handle the problems associated with unobserved heterogeneity better than most existing studies of discrimination. We find that, even when we control for all other differences, searchers who have non-Nordic names, are old or unemployed receive significantly fewer contacts. Moreover, we find that this matters for the hiring outcome: Searchers who receive more contacts have a higher probability of actually getting hired.
Keywords: J64; J71; 330; Job search; Unobserved heterogeneity; Discrimination; Personalbeschaffung; Personalauswahl; Arbeitskräfte; Arbeitsmarktdiskriminierung; Empirische Methode; Schweden